Análise das estratégias de produção em fornecedores de marcas próprias: estudo multicaso em empresas do setor de alimentos - Yokoyama, Marcos Hideyuki (2010)
The own-brand strategy has been adopted by wholesalers and retailers seeking competitive advantage through the commercialization of products sold under their brand names. The adoption of this strategy has created a new demand for the suppliers, which need to reevaluate their production structure to decide whether or not to manufacture such products. This research aims to identify and analyze the manufacturing strategy elements present in own brand supplier companies describing the motivations, positioning, and combinations of the content of the production strategy adopted. The first part comprises a literature review. In the empirical research, six case studies were carried out in companies which supply own brands in the food sector meeting the following criteria: suppliers that focus exclusively on own brands market; suppliers that sell national brand and own brand at the same time; and suppliers that sell both brands and have a representative national brand in the market it operates. Personal interviews were conducted with commercial or production managers based on semi-structured questionnaires prepared in accordance with the literature on the own brand strategy, competitive strategy, and manufacturing strategy. As a result of this research, it was possible to make some considerations about the characteristics of the suppliers pointing out the major differences between the literature and the data obtained in the empirical research with regard to the motivations for supplying and the characteristics related to production and commercialization. In addition, the companies were described according to their positioning strategies and were analyzed based on the generic production strategies adopted. Thus, based on such information, some relationships were established between the strategies adopted and the structural and infrastructure decisions, and the companies were evaluated based on the stage of their ownbrand evolution. Finally, new contributions were identified and suggestions for future research were put forward in an attempt to consolidate the knowledge of own brand suppliers in Brazil.